Prevalence and Risk Factors of Low Birth Weight in Tertiary Level Hospital in Eastern Nepal - Yadav, Amar Kumar; Yadav, Binod Kumar; Acharya, Alok; Mishra, Rimu (Journal of Nobel Medical College, 2025)
Background: The birth weight of the newborn determines of its survival, growth and development. World health organization defined low birth weight as weight at birth less than 2500 grams. Low birth weight baby die 20 times more than normal weight baby. There are 16% of the live birth are low birth weight worldwide. The prevalence of low-birth-weight newborn in Nepal was 12%.Materials and Methods: A cross-section study was under taken in the Nobel Medical College Teaching Hospital Biratnagar. All newborn babies delivered in the department of obstetrics and gynecology at Nobel Medical College Teaching Hospital during study period was under taken as sample size. The collected DATA were entered in software Microsoft Excel and transferred to SPSS version 27 and analysis was done.Results: The prevalence of low birth weight was 23.3% in our study. The low birth weight was significant associated with gestational age and parity of mother. The gestational age less than 37 weeks had more low birth weight 133(58.9%). Similarly, primi parous mother had high low birth weight146(61.3%) than multi parous mother. Conclusion: In our study we found that the low-birth-weight baby was more common in the mother with gestational age less than 37 weeks, primi parous and Janjati ethnicity.